RELATIONSHIP BETWEEN LAMENESS AND CRYPTORCHIDISM IN IRAQI HORSES - I. Salih, S.; M.A. Jawad , N. (The Iraqi Journal of Veterinary Medicine, 1992)
Fifteen horses were examined for lameness. Diagnosis of those cases indicated that all horses were inguinal Cryptorchid. Cryptorchidectomy were performed for 12 horses, all cases were healed completely and lameness symptoms dissappeared. This study suggest that cryptorchidectomy is the best treatment and also. eradication of Cryptorchidism.